Avaliação in vitro do potencial antiproliferativo de O-acilamidoximas e 1,2,4-oxadiazóis em linhagens de células tumorais - Dutra, Luana Letícia Alves (2019)
Cancer is a group with more than 100 diseases of genetic origin characterized by dysfunctions in the proliferation processes and cell death. Burkitt’s lymphoma is a high-grade B-cell cancer with a median overall survival of 2.7 months and very common in children. The synthesis of new compounds with antitumor potential can be a route for improving lymphoma treatment, therefore is expected they will have the ability to modulate oncogenic pathways. 1,2,4-Oxadiazoles are molecules with heteroaromatic ring system very relevant to the pharmaceutical industry, with recognized antitumor activity. The aim of this study was to evaluate the in vitro antiproliferative effect and the probably action mechanism of 1,2,4-oxadiazoles and their synthesis intermediates, O-acylamidoximes, against tumor cell lines. Ten pure substances were tested, 6 of the acylamidoxime class and 4 of the 1,2,4-oxadiazole class, using tests that evaluated cytotoxicity, cell viability, effect on cell cycle progression and pattern of cell death. Acylamidoximes showed cytotoxic activity against tumor lines with at least 75% inhibition of cell growth. The molecules showed IC50 values ranging from 6,87 to 14,24 µM in 72 hours, and DFA 52 and DFA 59 showed higher selectivity for the Burkitt Lymphoma derived cell line (RAJI). In the 48 hour assay, the IC50 values of DFA 52 and DFA 59 were 12,86 and 9,22 µM, respectively. The morphological analysis demonstrated prolongations formation in the cytoplasmic membrane of the treated cells. Flow cytometric analysis demonstrated that the molecules inhibited cell proliferation and caused membrane damage. In the cell cycle analysis was verified a significant increase of cells in phase G0/G1 when treated with the molecules in the concentrations of 12,85 and 25,70 µM DFA 52 and 18,43 µM DFA 59. The evaluation of the cell death pattern demonstrated that the molecules induce depolarization in mitochondria, indicating possible involvement in the intrinsic pathway of apoptosis. The phosphatidylserine externalization assay by Annexin V confirmed that the compounds are involved in the induction of apoptotic cell death. The results showed that the molecules DFA 52 and DFA 59 have activity against hematopoietic tumor cell lines, with greater selectivity for Burkitt lymphoma, and are promising to use as a tool in the formulation of compounds with anticancer activity.